REVEALING THE STICKY FLOOR EFFECT OF THE GENDER WAGE GAP IN INDONESIA BY USING AN UNCONDITIONAL QUANTILE REGRESSION WITH RIF-OLS APPROACH - Aisyah ‘Azizah Nur Rahmah; Wahyuni Andriana Sofa (PATTIMURA UNIVERSITY, 2026)
Gender inequality persists as an ongoing challenge, particularly evident in the persistent wage gap which often stems from entrenched societal perceptions that restrict women into subordinate roles. This study aims to investigate factors influencing wage gap and its explained and unexplained contributor. Many studies in Indonesia only measure gender wage gap at one average point. Each point of the wage distribution has different characteristics, so the gender pay gap at one average point cannot be assumed to apply to the entire wage distribution. This study uses a more up-to-date method to examine wage differences between gender. Besides, the use of the internet as part of digitalization is crucial as a factor that has not been widely explored in other researches. Using data from Sakernas February 2023, this study employs UQR with RIF-OLS estimation and Blinder-Oaxaca decomposition. The results show that regional status, secondary education, work experience, internet use, working hours, and union membership affect the wages of both male and female workers across quantiles. Blinder-Oaxaca decomposition shows that women receive 12.25 to 69.37 percent lower wages than men, and the pattern varies across different wage group, confirming a sticky floor effect. Furthermore, education, regional status, marital status, training, internet use, activity status, and union membership are proven to narrow the gap. The differences in worker characteristics by gender affect wage disparities, and the government is expected to address the widening gap, especially at the bottom of the wage distribution.